Нова знахідка Carex bohemica Schreb. (Cyperaceae) з Лівобережного лісостепу (Україна) - Жигаленко, О.А.; Данилик, І.М.; Андрієнко, Т.Л. (Український ботанічний журнал, 2009)
Сообщается о находке редкого вида Carex bohemica на территории Ичнянского национального природного парка (Черниговская обл.). Характеризуются растительные сообщества, в которых найден вид. The article provides information about a locality of a rare species Carex bohemica in the territory of Ichniansky National Nature Park (Chernihiv Region). Data on plant communities with the species are presented.